The Czech manuscripts : forgery, translation, and national myth - Cooper, David L., 1970- (Northern Illinois University Press, an imprint of Cornell University Press, 2023)
"A study of the nineteenth-century Czech forged manuscripts (Rukopis královédvorský and Rukopis zelenohorský) that examines the contexts of their creation and reception and their poetics"-- Provided by publisher.
Keywords: Hanka, Václav, -- 1791-1861. -- Rukopis Královédvorský.; Hanka, Václav, -- 1791-1861. -- Zelenohorský rukopis.; Rukopis Královédvorský (Hanka, Václav); Zelenohorský rukopis (Hanka, Václav); Czech literature -- 19th century.; Literary forgeries and mystifications -- History -- 19th century.; Nationalism and literature.; Faux et supercheries littéraires -- Histoire -- 19e siècle.; Nationalisme et littérature.; LITERARY CRITICISM / Russian & Former Soviet Union.; Czech literature; Literary forgeries and mystifications; Nationalism and literature; Museology & heritage studies.; Antiques, Collecting.; 1800-1899; Electronic books.; History